(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Service is comparatively a new object of geographical study. As sociologisation and humanization of geography raise interest in the study of regional differences in life quality of population, which mainly depends on the level of service. The main objectives of geography service: a) to identify patterns of territorial organization of service; b) to identify territorial differences in service development and to assess the level of service in different territorial units; c) to identify the characteristics of the service in different geographical conditions.